Pregled tehnologije brizganja prašnatih materialov - Berginc, Boštjan (Strojniški vestnik, 2005)
In this paper an overview of the powder injection moulding (PIM) process has been made. In the paper the process and shape restraints, alternative technologies, market niche and existing applications of the technology are described. Using PIM it is possible to produce highly complicated, micro and two-component parts. The mixtures used for PIM can also be used for thermoforming and blow moulding. In this paper are also presented the mechanical properties of the manufactured components and their dependence on the process parameters, chemical structure of powders and some metallurgic variables. Furthermore, the cost analysis comparison between the PIM and high speed cutting (HSC) is made. This paper is meant for the designers of new parts, who would like tp apply this technology and for certain individuals and companies who haven't come across this technology yet.
Keywords: brizganje prahu; pregledi tehnologij; omejitve; analize stroškov; metalurgija prahov; brizganje prahov